Tqm And Organizational Culture Change Requirements - Slimani, Ilies (Finance and Business Economies Review, 2019)
The organizational culture based on harmony and consistency among the members of the organization drives TQM to excellence, innovation and individual and collective initiatives. If that climate does not exist, the innovation will not improve. In other words, FAO management must change the organization's culture and values, adjust its organizational structure and guide supervision patterns in a manner consistent with the new TQM concept.